A Need Analysis of STEM-integrated Flipped Classroom E-module to Improve Critical Thinking Skills - Puspitasari, Reni Dwi; Herlina, Kartini; Suyatna, Agus (Universitas Islam Negeri Raden Intan Lampung, 2020)
In recent years, the flipped classroom and STEM learning approach has become one of the interesting studies in Education. Various researches were conducted to determine their impact on learning. This research is a descriptive survey conducted to determine the needs of teachers and students about e-module with the STEM integrated flipped classroom. Data were collected using a questionnaire with 15 respondents who work as physics teachers in Lampung Province and 30 respondents from grade XI students in one of the high schools in Bandar Lampung. Based on the survey results, we concluded that (1) 86% of physics teachers stated that they needed a STEM-integrated flipped classroom e-module, and (2) 78% of students stated that they were interested in learning by using a STEM-integrated flipped classroom e-module. So it is clear that physics teachers and students in Lampung need e-modules with a flipped classroom approach and integrated STEM.